2020
DOI: 10.1155/2020/9145458
|View full text |Cite
|
Sign up to set email alerts
|

Sesamin Promotes Neurite Outgrowth under Insufficient Nerve Growth Factor Condition in PC12 Cells through ERK1/2 Pathway and SIRT1 Modulation

Abstract: e promotion of neurogenesis can be a promising strategy to improve and restore neuronal function in neurodegenerative diseases. Nerve growth factor (NGF) plays a key role in neurite outgrowth and synaptic formation during brain repair stage. Nowadays, there are several studies on the developing methods to enhance the endogenous NGF activity for treatment and restore the neuronal function. In this study, the potentiating effect of sesamin, a major lignan in sesame seeds (Sesamum indicum) and oil, on NGF-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
3
9
0
Order By: Relevance
“…A recent study revealed that glutamate acts as an inhibitory neurotransmitter in the olfactory system [55]. Furthermore, previous in vitro studies using mammalian cultured cells showed that sesamin promoted neurite outgrowth under insufficient nerve growth factor conditions in rat pheochromocytoma cells [8]. Considering these previous findings, our observations suggest that sesamin might suppress age-dependent impairment of long-term memory.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…A recent study revealed that glutamate acts as an inhibitory neurotransmitter in the olfactory system [55]. Furthermore, previous in vitro studies using mammalian cultured cells showed that sesamin promoted neurite outgrowth under insufficient nerve growth factor conditions in rat pheochromocytoma cells [8]. Considering these previous findings, our observations suggest that sesamin might suppress age-dependent impairment of long-term memory.…”
Section: Discussionsupporting
confidence: 72%
“…Sesame seeds have been used as a traditional health food supplement, as well as medicinal remedy [1,2]. They contain lignans that can significantly reduce various health risks [3][4][5][6][7][8]. Sesamin is the most abundant lignan in sesame seeds, and the catechol moiety of the sesamin molecule is responsible for the antioxidant and anti-inflammatory properties of sesame in mammals [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies highlighted the crucial role of NGF in neurogenesis, cognition, and brain repair, indicating the importance of maintaining NGF levels to prevent the occurrence of neurotoxicity [45][46][47]. In the current study, the lowest levels of NGF obtained by administering Dox alone were successfully elevated after adding C. macrocarpa combined with Dox.…”
Section: Discussionsupporting
confidence: 53%
“…Sesamol, sesamin, and sesamolin are the major bioactive compounds in Sesami Semen Nigrum. Among them, sesamol was reported to have significant neuroprotective activity [ 33 ] and sesamin was shown to possess the function of stimulating NGF-induced neurogenesis [ 34 ]. In Caenorhabditis elegans , both sesamin and sesamolin have shown protective ability in alleviating A β -induced toxicity and reducing the formation of A β oligomers [ 35 ].…”
Section: Discussionmentioning
confidence: 99%